Trans-nasal puncture for bilateral congenital choanal atresia - Sahebpor Alireza; Ghaffari Vajihe; Elisay Ali (Journal of Indian Association of Pediatric Surgeons, 2006)
Aims: There are many surgical techniques to repair bilateral congenital choanal atresia, among them trans-nasal approach with simple puncture, dilation and stenting technique is most frequently used. We describe a series of trans-nasal puncture and stenting technique, by using pediatric urethral sounds and nalaton N 14. Materials and Methods: We used this technique in 10 patients with equal sex distribution, between 1997 and 2004 in our hospital. Mean age at operation was 3.5 days. Mean duration of stenting was 33.6 days (2-8 weeks) and patients were followed for an average duration of 28.8 months after surgery. Results: Three patients (30%) developed re-stenosis after stent removal, which was easily managed by simple dilatation and re-stenting for more two weeks. There was a minimal operative bleeding with no infection or central nervous system trauma. Conclusion: This safe, simple operation by using pediatric urethral sounds is a non-expensive way to treat this anomaly with a low complication rate.